Immigration and STEM: Qualified immigration from India showing signs of success - Oliver Koppel; Axel Plünnecke (Institut der deutschen Wirtschaft (IW), 2017)
In recent years, qualified immigration has started to play a significant role for the German labour market, especially for securing skilled STEM (science, technology, engineering, and mathematics) employment. Efforts made to attract STEM immigrants from India are starting to show signs of success - both the number of employees in academic STEM jobs and the number of students in STEM disciplines have increased significantly in recent times. From a strategic viewpoint, this immigration from demographically strong non-European countries is particularly important for the future. – – Bereits in den letzten Jahren haben Zuwanderer erheblich zur Fachkräftesicherung in MINT-Berufen beigetragen. Bestrebungen, MINT-Zuwanderer aus dem Herkunftsland Indien zu gewinnen, zeigen erste Erfolge - sowohl die Zahl der Beschäftigten in akademischen MINT-Berufen als auch die Zahl der Studierenden in MINT-Fächern sind zuletzt deutlich gestiegen.
Keywords: 330